Comparison of Extraction Solvents Towards Anti-Propionibacterium acnes activity of Alphitonia incana (Roxb). Teijsm. & Binn. ex Kurz Leaves - Hafiz Ramadhan; Rahmi Muthia; Sari Wahyunita; Dyera Forestryana; Sherly Mar'atu Soleha; Lihimi Lihimi (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz locally known as Balik Angin in Borneo Island is one of the endemic plants that have the potential to be an alternative antibacterial agent. Balik Angin leaves contain secondary metabolites that have to play a role to inhibit the growth of Gram-positive bacteria. This study aimed to compare the different extraction solvents which are methanol and ethanol on the maceration of Balik Angin leaves in producing antibacterial activity against Propionibacterium acnes. The leaves were macerated using methanol and ethanol respectively. Antibacterial assay was carried out by the Well diffusion method. The results showed minimum inhibitory concentration (MIC) of ethanol extract which is 3.2% has a diameter of clear zone of 9.475±0.311 mm. Meanwhile, the methanolic extract with a similar MIC has a lower diameter of clear zone of 2.55±0.85 mm. The results correlate with the number of secondary metabolites groups that were identified based on phytochemical screening in ethanol extract containing alkaloid, phenolic, flavonoid, tannin, saponin, and phytosteroid, however, methanol extract not containing alkaloid. The conclusion of this study is ethanol solvent more effective to extract secondary metabolites from Balik Angin leaves compare to methanol solvent, so that can produce more powerful anti-Propionibacterium acnes activity.